Fusion RNA profiling provides hints on cell of origin of mysterious tumor - Xie, Zhongqiu (Mol Cell Oncol, 2016)
Biological samples can be grouped into separate clusters based on their gene expression profiles. This approach has yielded meaningful biological insights and facilitated biomarker discoveries. Recently, we developed another approach to study connections between biological samples based on their fusion RNA expression. We have used this approach to provide insights into the cell of origin for a mysterious tumor, alveolar rhabdomyosarcoma.